At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's solve the equation [tex]\(2^{x-3} \cdot 2 \cdot a^{1-x} = 2^{3x-5} \cdot a^{x-2}\)[/tex].
### Step-by-Step Solution:
1. Combine the Exponents of 2:
First, notice that we can combine the terms involving the base 2 on each side.
The left side [tex]\(2^{x-3} \cdot 2\)[/tex] can be rewritten as:
[tex]\[ 2^{x-3} \cdot 2^1 = 2^{(x-3) + 1} = 2^{x-2} \][/tex]
So our rewritten equation now becomes:
[tex]\[ 2^{x-2} \cdot a^{1-x} = 2^{3x-5} \cdot a^{x-2} \][/tex]
2. Compare the Exponents of 2:
Since we have [tex]\(2^{something}\)[/tex] on both sides, we can compare the exponents:
[tex]\[ x-2 = 3x-5 \][/tex]
3. Solve for x:
To solve for [tex]\(x\)[/tex], we isolate [tex]\(x\)[/tex] by first subtracting [tex]\(x\)[/tex] from both sides:
[tex]\[ x - 2 - x = 3x - 5 - x \][/tex]
Simplify to:
[tex]\[ -2 = 2x - 5 \][/tex]
Next, add 5 to both sides:
[tex]\[ -2 + 5 = 2x \][/tex]
Simplifies to:
[tex]\[ 3 = 2x \][/tex]
Finally, divide by 2:
[tex]\[ x = \frac{3}{2} \][/tex]
So the solution to the equation [tex]\(2^{x-3} \cdot 2 \cdot a^{1-x} = 2^{3x-5} \cdot a^{x-2}\)[/tex] is:
[tex]\[ x = \frac{3}{2} \][/tex]
### Step-by-Step Solution:
1. Combine the Exponents of 2:
First, notice that we can combine the terms involving the base 2 on each side.
The left side [tex]\(2^{x-3} \cdot 2\)[/tex] can be rewritten as:
[tex]\[ 2^{x-3} \cdot 2^1 = 2^{(x-3) + 1} = 2^{x-2} \][/tex]
So our rewritten equation now becomes:
[tex]\[ 2^{x-2} \cdot a^{1-x} = 2^{3x-5} \cdot a^{x-2} \][/tex]
2. Compare the Exponents of 2:
Since we have [tex]\(2^{something}\)[/tex] on both sides, we can compare the exponents:
[tex]\[ x-2 = 3x-5 \][/tex]
3. Solve for x:
To solve for [tex]\(x\)[/tex], we isolate [tex]\(x\)[/tex] by first subtracting [tex]\(x\)[/tex] from both sides:
[tex]\[ x - 2 - x = 3x - 5 - x \][/tex]
Simplify to:
[tex]\[ -2 = 2x - 5 \][/tex]
Next, add 5 to both sides:
[tex]\[ -2 + 5 = 2x \][/tex]
Simplifies to:
[tex]\[ 3 = 2x \][/tex]
Finally, divide by 2:
[tex]\[ x = \frac{3}{2} \][/tex]
So the solution to the equation [tex]\(2^{x-3} \cdot 2 \cdot a^{1-x} = 2^{3x-5} \cdot a^{x-2}\)[/tex] is:
[tex]\[ x = \frac{3}{2} \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.